Influence of successive badminton matches on muscle strength, power, and body-fluid balance in elite players - Abian-Vicen, J.; Castanedo, A.; Abian, P.; Gonzalez-Millan, C.; Salinero, J. J.; Del Coso Garrigos, J. (International Journal of Sports Physiology and Performance, 2014)
The aim was to analyze the influence of competitive round on muscle strength, body-fluid balance, and renal function in elite badminton players during a real competition. Body mass, jump height during a countermovement jump, handgrip force, and urine samples were obtained from 13 elite badminton players (6 men and 7 women) before and after the 2nd-round and quarterfinal matches of the national Spanish badminton championship. Sweat rate was determined by using prematch-to-postmatch body-mass change and by weighing individually labeled fluid bottles. Sweat rates were 1.04 ± 0.62 and 0.98 ± 0.43 L/h, while rehydration rate was 0.69 ± 0.26 and 0.91 ± 0.52 L/h for the 2nd round and quarterfinals, respectively. Thus, dehydration was 0.47% ± 1.03% after the 2nd round and 0.23% ± 0.43% after the quarterfinals. There were no differences in prematch-to-postmatch jump height, but jump height was reduced from 37.51 ± 8.83 cm after the 2nd-round game to 34.82 ± 7.37 cm after the quarterfinals (P < .05). No significant differences were found in handgrip force when comparing prepost matches or rounds, although there were significant differences between dominant and nondominant hands (P < .05). The succession of rounds caused the appearance of proteinuria, hematuria, glycosuria, and higher nitrite and ketone concentrations in urine. Rehydration patterns during a real badminton competition were effective to prevent dehydration. A badminton match did not affect jump height or handgrip force, but jump height was progressively reduced by the competitive round. Badminton players` renal responses reflected diminished renal flux due to the high-intensity nature of this racket sport.